PENANAMAN NILAI UKHUWAH ISLAMIYAH MASYARAKAT MELALUI KEGIATAN YASINAN DI NGRAYUN - BAOSAN LOR - Rohmatul Khusna, Eva; Fahri, Tri Amal; Rifa’i, Muh.; Rohani, Imam (Institut Agama Islam Riyadlotul Mujahidin, 2023)
Humans are individual creatures as well as social beings, who actually as humans have unique and different characters from one another, and need a calm atmosphere, and time to think about themselves, privacy. However, as social beings, humans also need other people to interact, and need groups to acknowledge their existence. The need to interact and socialize is a natural invention or human nature. Islamic ukhuwah in society is a form of solidarity carried out through love for brothers and sisters who have become a tradition of the people of Baosan Lor. This tradition is a principle that contains religious values ​​and teachings passed down by the Prophet to his people by helping each other, caring for each other and strengthening the stronghold of faith among fellow believers in terms of ukhuwah.